2017
DOI: 10.1111/ahe.12279
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Evaluation of the Thoracolumbar Nerves Related to the Transversus Abdominis Plane Block Technique in the Dog

Abstract: Transversus abdominis plane (TAP) is a fascial plane containing the thoracolumbar nerve branches that innervate the abdominal wall. Limited information is available on the anatomical organization of these nerve branches in the dog, which is of great importance for the success of the TAP block anaesthetic technique. The aim of this study was to describe the origin and conformation of thoracolumbar nerves running through the TAP in 20 hemi-abdominal walls of 10 adult mongrel dog cadavers with an average body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…The dogs admitted to UVH, UPM were mostly local breed and stray dogs; hence, it is expected to be overrepresented in this study. Despite various breeds in the study, the spinal anatomy between breed, size or age are comparable (Bodh et al, 2016; -Herrera et al, 2017); thus, it is less likely to affect the nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The dogs admitted to UVH, UPM were mostly local breed and stray dogs; hence, it is expected to be overrepresented in this study. Despite various breeds in the study, the spinal anatomy between breed, size or age are comparable (Bodh et al, 2016; -Herrera et al, 2017); thus, it is less likely to affect the nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The canine abdominal wall receives innervation from spinal nerves T7 to L3 and, as previously mentioned, dogs have a 13 th thoracic vertebrae (and subsequent rib and spinal nerve) that is absent in humans [46,47,[71][72][73]. Interestingly, in dogs, the umbilicus is innervated by T10 as it does in humans [47,71].…”
Section: Nervesmentioning
confidence: 99%
“…Additionally, there is considerable variation in the course of the canine upper thoracic nerves from T7 to T9 and their presence in the TAP. Often, only the spinal nerves from T10 to L2 are found within the TAP of dogs [72]. Similarly, in primates, the upper T8 and T9 are occasionally absent from the TAP overlying the transversus abdominis [53].…”
Section: Nervesmentioning
confidence: 99%
“…This locoregional technique involves the infiltration of local anaesthetic into the fascial plane between the internal oblique and transversus abdominis muscles to block the sensory components of the abdominal wall. Recently, the TAP block has been introduced in veterinary anaesthesia, both in experimental and clinical settings [4][5][6][7]. This technique involves injecting a volume of local anaesthetic into the neurovascular plane between the transversus abdominis and internal oblique muscle in order to saturate somatic afferents before they leave the TAP and provide analgesia in that anatomical area [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical studies carried out in dogs showed that the nerves involved in TAP are the ventral branches of T11-T13 and L1-L3. These nerves are the target of the anaesthetic block in this plane [5,11]. Using the ultrasound-guided (US-guided) technique, the TAP can be correctly identified and, both the needle trajectory and injectate spread can be performed between the IO and TA muscle layers with accuracy and safety, potentially reducing the risk of block failure, accidental intraperitoneal injection, and injury to adjacent structures [14,15].…”
Section: Introductionmentioning
confidence: 99%